Greater risk for more money: the economics of negotiating condom use amongst sex workers in South Africa. Issue 9 (2nd September 2019) - George, Gavin; Nene, Siphumelele; Beckett, Sean; Durevall, Dick; Lindskog, Annika; Govender, Kaymarlin
ABSTRACT : The economics of sex work and the effect on safe sex practices remain understudied. This research contributes to a better understanding of how economic opportunity and vulnerability place sex workers (SWs) at an increased risk of STI infection. Using quantitative and qualitative methods, we investigated the role of economic incentives in determining condom use among SWs. The data reveals that SWs are on average, nearly doubling their rates for condomless sex. Our findings that SWs are engaging in condomless sex to increase their earnings, illustrates the point that the context in which they operate influences condom negotiation and consequently, increases risky sexual behaviour.